Managing BOS Fund: The Role of Transparency, IT, and Accountability in Surakarta School - Aprilita, Ruth; Saptantinah, Dewi (Universitas Bhayangkara Surabaya, 2025)
This study examines the influence of transparency, the utilization of information technology, and accountability on the management of School Operational Assistance (BOS) funds. Employing a quantitative approach, primary data were collected from 84 respondents including principals, treasurers, and committee members from all public junior high schools in Surakarta through a saturated sampling technique. Data analysis was conducted by testing the research instruments using validity, reliability, and classical assumption tests, followed by multiple linear regression analysis. The findings reveal that both transparency and the adoption of information technology exert a significant positive effect on the effectiveness of BOS fund management. In other words, fund management improves when public information is made accessible and supported by information systems that facilitate efficient communication. In contrast, financial accountability did not demonstrate a significant effect, implying that compliance with standard operating procedures alone does not necessarily enhance fund management practices. Moreover, the regression model employed was shown to significantly predict effectiveness, accounting for a substantial proportion of the observed variance.